Adjuvant chemotherapy improves survival outcomes after complete resection of thymic squamous cell carcinoma: a retrospective study of 116 patients. (20th June 2021) - Gao, Lanting; Wang, Changlu; Liu, Mina; Fang, Wentao; Lv, Changxing; Fu, Xiaolong
Abstract: OBJECTIVES: The aim of this study was to evaluate the efficacy of adjuvant chemotherapy (ACT) for thymic squamous cell carcinoma after completely resection. METHODS: Patients with thymic squamous cell carcinoma treated with complete resection between January 2009 and December 2016 were retrospectively identified. Kaplan–Meier analysis was used to summarize the time-to-event variables. Univariable and multivariable Cox proportional hazards regression analyses were performed. RESULTS: A total of 116 patients were analysed with 44 patients in the non-ACT group and 72 patients in the ACT group. No significant difference was found in the 5-year recurrence-free survival (RFS) rate (58.1% vs 51%, P  = 0.33) or the 5-year overall survival (OS) rate (77.7% vs 67.1%, P  = 0.26) between the ACT group and the non-ACT group. Masaoka stage was the only independent prognostic factor for both RFS and OS. Subgroup analysis showed significant improvement in 5-year RFS for Masaoka stage II patients ( P  = 0.035) and 5-year OS ( P  = 0.036) for Masaoka stage III patients when comparing ACT with non-ACT. No chemotherapy-related death occurred. The most frequent adverse effect higher than grade 3 was neutropenia. CONCLUSIONS: For completely resected thymic squamous cell carcinoma, ACT significantly improved the 5-year RFS in Masaoka stage II patients and the 5-year OS in Masaoka stage III patients. Abstract : Thymic carcinoma is a rare but aggressive neoplasm of the anterior mediastinum, with 5-year survival rates ranging from 28% to 67% [1, 2].